An Observational Case Study on Ayurvedic Treatment Regime on Kitibha Kushta (Psoriasis) - Fernando, S.P.H.; Weerasekara, K.R. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Kitibha kushta, identified under Kshudra kushta in Ayurvedic texts, closely resembles psoriasis in modern dermatology. It is mainly caused by an imbalance of Vata and Kapha doshas along with impurities in the blood. Classical signs include dryness, itching, roughness, and dark skin discoloration. This observational case study was conducted to explore the effectiveness of Ayurvedic treatments for Kitibha kushta, based on principles from the Charaka Samhita and Sushruta Samhita. Two patients were selected and treated with an individualized Ayurvedic approach over of a period of one and half month. While Kitibha kushta is primarily a Vata-Kapha disorder, the clinical features observed in these cases indicated predominantly Pitta and Rakta involvement. Therefore, the treatment plan included both pacifying therapies for vitiated Dosha. This approach allowed for a more comprehensive management of the disease process. The treatment began with improving digestion and toxin removal using Triphal guggul decoction and Manibadra churna with the externally Panchavalkala avagaha sweda and Pinda oil application. This was followed by internal purification through medicated ghee intake using Go-Ghrita via the Vardhamana method till the Samyak snigdha lakshana present. After that Sweda karma such as Nadi sweda, and purgation with Trivrut kashaya. After purification, Samana therapies were administered, including Arogyavardhani vati, Gokshuradi guggulu, and Chandraprabha vati, along with local application of Pinda taila and Neelyadi taila. The outcomes showed significant improvement in skin texture, scaling, discoloration, and itching. The treatment helped in balancing the doshas and breaking the disease process, especially through Pitta-Rakta shodhana and calming of KaphaVata. These positive results indicate that Ayurvedic care, when properly administered, very effective in managing Kitibha kushta. Further research involving larger groups is recommended to strengthen evidence and expand access.
Keywords: Kapha; Kitibha; Kshudra; Kushta; Shodhana; Sweda karma; Vata